Peran Balai Karantina Bandar Lampung dalam Penegakan Hukum Pidana terhadap Tindak Pidana Penyelundupan Satwa Burung - Zercy Nurjannah; Rinaldy Amrullah; Emilia Susanti; Budi Rizky Husin; Muhammad Farid (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Animal quarantine plays a crucial role in preventing the smuggling of wildlife, particularly protected bird species. Although this is regulated under Law Number 21 of 2019 concerning Animal, Fish, and Plant Quarantine, smuggling practices remain prevalent. This study employs a normative and empirical juridical approach to examine the role of the Agricultural Quarantine Agency Class 1A Bandar Lampung in combating bird smuggling, as well as the factors hindering the enforcement of criminal law. The findings indicate that the quarantine agency carries out three main roles: normative (based on regulations), factual (preventive and repressive actions), and ideal (emphasizing prevention). Obstacles faced include a shortage of field personnel, limited equipment and funding, and low public awareness of the law. It is recommended that the quarantine agency improve community welfare and collaborate with relevant institutions to optimize public outreach and law enforcement efforts.